Resultados del bypass gástrico en diabéticos tipo 2 con índice de masa corporal menor a 35 Kg/m - Lanzarini S., Enrique; Molina F., Juan C.; Lara V., Ivone; Csendes J., Attila (Revista Hospital Clínico Universidad de Chile, 2012)
Currently type 2 diabetes and obesity behave as epidemic diseases. Medical treatment achieved adequate metabolic control in a insufficient number of patients and is not exempt of complications. Mean while the group of diabetics with severe and morbid obesity that have been submitted to bariatric surgery have evolved mostly with remission of their diabetes in medium and long term, so that surgery has become the first choice of treatment. There mision that ensue early in the postoperatory, is not only explained by weight loss, other mechanisms ligated to anatomic and functional changes mediated by surgery are under research. There is a great interest to explore new treatment options for type 2 diabetes including surgery, for patients with mild to severe obesity, with very good initial results.